Meat product consumption among children aged 1–3 years in Baquba City, Iraq - Noaman, Aqeel Abbas; Mohammad, Sarmad Qassim (Intelektual Pustaka Media Utama, 2025)
The caregiver should prioritize meats in the infant's diet during the last 6 months due to their sources of nutrients and proteins. This study aimed to identify the prevalence of meat product consumption among children aged 1–3 and their preferences based on age and sex. We conducted an analytical cross-sectional study on 810 children aged 1–3 years using a questionnaire. We used the chi-square test, and a p-value < 0.05 was considered significant. The study found that 60.3%, 86.2%, 85.4%, and 59.3% consumed red meat weekly (p ≤ 0.001), fish monthly (p ≤ 0.001), chicken weekly (p ≤ 0.001), and eggs daily (p ≤ 0.001), respectively. The second-year children prefer to consume red meat (44.8%), fish (46.3%), chicken (45.2%), and eggs (44.2%) more frequently than in other years. Males preferred red meat, fish, chicken, and eggs more than females (54.1% vs. 45.9%; 52.7% vs. 47.3%; 54.5% vs. 45.5%, and 54.4% vs. 45.6%), respectively. In conclusion, the consumption of chicken and eggs is more prevalent. In the second year of life, children, particularly boys, consume more meat products due to their own or their parents' preferences. We suggest expanding the scope of this study to include dairy products.